Teaching Collaborations in Elementary Schools: Teachers' Understanding, Strategies, and Obstacles - Ulin Nuskhi Muti'ah; Heri Retnawati; Anwar Senen; Gulzhaina K. Kassymova (Al Ibtida: Jurnal Pendidikan Guru MI, 2021)
Abstract Collaborative skills are becoming mandatory in the 21st century. There have been many studies that show the effectiveness of the collaborative learning (CL) approach on students' collaboration and interaction abilities. In Indonesia, through the implementation of 2013 curriculum, group learning is encouraged. This study aims to describe the implementation of collaborative learning by describing the teachers' understanding of collaborative skills and collaborative learning models, the strategies teachers use to teach collaborative skills, and the constraints that prevent teachers from using collaborative learning models. This qualitative research involved 13 elementary school teachers in the Special Region of Yogyakarta Province. Data collection was carried out through in-depth interviews. Data were analyzed using the Bogdan and Biklen models. The results show that 1) the teachers' understanding of collaborative skills still needs to be improved, especially in the collaboration aspect, 2) the teachers' knowledge about collaborative learning models is still lacking, 3) the obstacles that cause teachers not to use CL are teachers' lack of knowledge, teachers’ lack of motivation to improve their knowledge, teachers’ hesitance to try new learning models, and teachers' concerns that it will be difficult for students to use CL. Therefore, the teachers need to increase their understanding and open themselves to new learning models. This can be a concern for principals and teacher education managers to provide intensive education and training related to collaborative learning approach.Keyword: collaborative learning, teachers’ understanding, elementary schools. AbstractKeterampilan kolaboratif menjadi keterampilan wajib di abad ke-21. Telah banyak penelitian yang menunjukkan efektivitas pendekatan pembelajaran kolaboratif terhadap kemampuan kolaborasi dan interaksi siswa. Di Indonesia, melalui penerapan kurikulum 2013, pembelajaran kelompok digalakkan. Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan pembelajaran kolaboratif dengan mendeskripsikan pemahaman guru tentang keterampilan kolaboratif dan model pembelajaran kolaboratif, strategi yang digunakan guru untuk mengajarkan keterampilan kolaboratif, dan kendala yang menghalangi guru menggunakan model pembelajaran kolaboratif. Penelitian kualitatif ini melibatkan 13 guru SD di Daerah Istimewa Yogyakarta. Pengumpulan data dilakukan melalui wawancara mendalam. Data dianalisis menggunakan model Bogdan dan Biklen. Hasil penelitian menunjukkan bahwa 1) pemahaman guru tentang keterampilan kolaboratif masih perlu ditingkatkan terutama pada aspek kolaborasi, 2) pengetahuan guru tentang model pembelajaran kolaboratif masih kurang, 3) kendala yang menyebabkan guru tidak menggunakan pembelajaran kolaboratif adalah kurangnya pengetahuan guru, kurangnya motivasi guru untuk meningkatkan pengetahuannya, keengganan guru untuk mencoba model pembelajaran baru, dan kekhawatiran guru akan kesulitan siswa dalam menggunakan pembelajaran kolaboratif. Oleh karena itu, guru perlu meningkatkan pemahaman dan membuka diri terhadap model pembelajaran baru. Hal ini dapat menjadi perhatian bagi kepala sekolah dan pengelola pendidikan guru untuk memberikan pendidikan dan pelatihan secara intensif terkait dengan pendekatan pembelajaran kolaboratif.Kata kunci: pembelajaran kolaborasi, pemahaman guru, sekolah dasar.